Answer:
[tex]5^2 \text{ or } 25[/tex]
Step-by-step explanation:
We can use exponent rules to simplify the expression:
[tex]\displaystyle \dfrac{(5^2)^{-3}\cdot 5^4}{5^{-4}}[/tex]
First, we can simplify the power to a power term with the rule:
- [tex](x^a)^b = x^{ab}[/tex]
↓↓↓
[tex]\displaystyle \dfrac{5^{2(-3)}\cdot 5^4}{5^{-4}}[/tex]
[tex]= \displaystyle \dfrac{5^{-6}\cdot 5^4}{5^{-4}}[/tex]
Next, we can combine the terms on the top using the multiplication of base rule:
- [tex]x^a\cdot x^b=x^{(a+b)}[/tex]
↓↓↓
[tex]\displaystyle \dfrac{5^{(-6 + 4)}}{5^{-4}}[/tex]
[tex]= \dfrac{5^{-2}}{5^{-4}}[/tex]
Finally, we can use the quotient of base rule:
- [tex]\dfrac{x^a}{x^b} = x^{(a-b)}[/tex]
↓↓↓
[tex]5^{(-2-(-4))}[/tex]
[tex]=5^{(-2+4)}[/tex]
[tex]\boxed{=5^2 = 25}[/tex]